Wnt/β-catenin signaling pathway activation reverses gemcitabine resistance by attenuating Beclin1-mediated autophagy in the MG63 human osteosarcoma cell line - Tao, Hao (Mol Med Rep, 2017)
Anaberrant Wnt/β-catenin signaling pathway is frequently implicated in tumorigenesis. However, whether the Wnt/β-catenin pathway plays a role in resistance to antitumor chemotherapy drugs remains unknown. In the present study, the process of autophagy was assessed following overexpression of the autophagy-associated gene Beclin 1 in gemcitabine-induced MG63 human osteosarcoma cells. Autophagy-associated gene expression was measured following activation or inhibition of the Wnt/β-catenin pathway in gemcitabine-induced MG63 cells using reverse transcription-quantitative polymerase chain reaction. In addition, the percentage of MG63 cell apoptosis was measured by flow cytometry following Wnt/β-catenin pathway activation or inhibition. The results demonstrated that Beclin 1 overexpression induced autophagy and reduced gemcitabine-induced apoptosis in MG63 human cell line. Furthermore, activation of the Wnt/β-catenin signaling pathway attenuated autophagy and enhanced gemcitabine-induced apoptosis. Additionally, the expression of Beclin 1 was reduced following Wnt/β-catenin signaling pathway activation. The present study demonstrated that activation of the Wnt/β-catenin signaling pathway may rescue chemotherapy drug resistance by downregulating the expression of Beclin 1.